Bringing elder abuse out of the shadows: a study from the old age homes of Davangere district, Karnataka, India - Achappa, Santosh; Rao, B. A. Varadaraja; Holyachi, Sharankumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Elder abuse is a violation of human rights. Elder abuse has disturbing consequences for older persons such as poor quality of life, psychological distress, and loss of property and security. It is also associated with increased mortality and morbidity.Objective of the study was to identify the magnitude and the pattern of elder abuse experienced by the elderly, which made them to join old age home. Methods: The study was a cross sectional study carried out in the old age homes of Davangere district, Karnataka, India for a period of 1 year with the sample of about 105 elderly residing in old age homes. Results: Out of 105 elderly, majority were in the age group of 60 – 69 (48%). Females (65%) outnumbered the males (35%). Majority of the residents were from rural background (71%). The magnitude of elder abuse in our study was found to be 35.2%. Regarding the type of elder abuse, majority of the residents experienced verbal abuse (70%) followed by physical abuse (13%). Daughter-in-law was involved in majority of the cases of elder abuse i.e., (45.9%), followed by their son (24.3%). Conclusions: The magnitude of elder abuse is on the higher side in our study, which made them to join old age home. This finding, questions the general perception in India whether the families are the safest place for the elderly to live.